Effect of stubborn disease on growth, yield and fruit quality of Frost Washington Navel and Frost Valencia oranges in Cyprus - Kyriakou, A. P.; Eliades, G.; Kapari-Isaia, Th; Ioannou, Nicolas (My University, 1996)
The effect of stubborn disease on growth, yield and fruit quality of orange cultivars Frost Washington Navel and Frost Valencia was studied over the period 1984-1994 in Akhelia, Cyprus. Cumulative two-year yield of 'Navel' and nine-year yield of 'Valencia' orange were reduced by 19% and 34%, respectively. Growth of 'Navel' trees was not affected by the disease, whereas growth of 'Valencia' was reduced by 11%. In both healthy and infected 'Valencia', tree growth (trunk circumference) was linearly related to annual fruit yield. Stubborn disease affected significantly the size, weight and quality of fruits in both cultivars. Compared with fruit from healthy trees, mean fruit weight of infected 'Navel' and 'Valencia' oranges decreased by 28% and 30%, respectively, and mean fruit diameter by 12% in both varieties. Total acidity was higher and the ratio of total soluble solids to total acids was lower in both 'Navel' and 'Valencia' fruits from infected trees.